Postpartum Mother's Knowledge about the use of Postpartum Contraceptive - Husnul Muthoharoh (Publikasi oleh Fakultas Kedokteran Universitas Islam Malang, 2021)
Most Mothers have difficulty in determining the exact type of contraception in the puerperium, because the mother has not previously understood about contraception to be used, this study aims to determine the post-partum mothers knowledge about contraception in the puerperium in Dlanggu Village, Kec. Deket, Kab. Lamongan.Design used in this study is descriptive Using a population of 30 respondents, the sample of 30 people with positive sampling techniques and analysis of the questionnaire as a measuring tool used is the frequency and distribution of research results obtained are good enough, lacking.The study found almost half of respondents who have sufficient knowledge about contraception is 14 (46.7%) respondents, and almost half again the respondents had less knowledge about contraception in the puerperium of 11 (36.7%) respondents.Conclusionof this study was almost half a per cent of respondents knowledgeable enough about contraception. So health officials are expected to conduct counseling to assist clients in selecting and deciding the type of contraception that will be used according to choice.